Management of BOS Fund Utilization in Improving Facilities and Infrastructure at SDN Pondoksirap, Bandung Regency - H. Soro , Suharyanto; Restiningsih, Tely; Dewi, Ineu Kenanga (Global Education Journal, 2025)
The School Operational Assistance Fund (BOS) program is one of the government programs that emerged from the policy in the field of education. The purpose of the School Operational Assistance (BOS) fund is to support school operations to be more optimal. This fund is used to help with non-personnel operational costs for elementary and secondary education units that implement compulsory education programs, including helping to reduce education costs for students, especially those from underprivileged families. SDN Pondoksirap is one of the public elementary schools that received BOS to help develop the quality of education in schools. This study aims to describe the role of BOS funds in improving facilities and infrastructure at SDN Pondoksirap, Bandung Regency. The method used in the research used is qualitative descriptive. To achieve this goal, a literature review research method was used, namely a study of the concepts and theories used based on available literature. The results of the literature study research stated that the implementation of the development of the eight education standards was effective and optimal due to the support of BOS funds. The implementation and improvement of the quality of education in schools can be realized through the use of BOS funds. The conclusion of this study is that BOS funds have a very important, strategic, and contributive role in the smooth and successful implementation and improvement of the quality of education.